IN-VITRO ANTIOXIDANT AND ANTILIPOLYTIC ACTIVITY OF MARINE ACTINOBACTERIA ISOLATED FROM PULICAT LAKE, TAMILNADU, INDIA - R RADHIKA; K AMUTHA (International Journal of Pharma and Bio Sciences, 2016)
The present study is undertaken to investigate antioxidant and pancreatic lipase inhibitory activity of ethyl acetate extract of actinobacteria isolated from sediment, soil samples of Pulicat Lake, Tamil Nadu, India. The Pancreatic Lipase Inhibitory activity of solvent extract was tested against Pancreatic Lipase enzyme using olive oil as the substrate. To evaluate the antioxidant activity the broth culture of the production medium was used for fermentation process and extracellular metabolites were extracted using the solvent ethyl acetate. The brown color extract obtained was dissolved in methanol and screened for DPPH radical scavenging activity. Out of the 110 isolates tested more than 50% of actinobacteria showed both antioxidant and antilipase activity. The findings of the present study suggested that the metabolites of marine actinobacteria isolated from Pulicat Lake, Tamil Nadu, India may be useful as antioxidants and anti-obesity agents.